Research methods for detecting unknown signals - Bezruk, V.M.; Ivanenko, S.A. (Radiotekhnika, 2017)
The introduction of new radio systems is limited by the loading of frequency bands and the inefficient use of the frequency resource. To solve this problem the technology of cognitive radio was developed. This technology requires the usage of signal detection algorithms. This will allow finding of free parts of the spectrum, with the purpose of their further use. However, most of the algorithms require knowledge of certain information about detecting signals. However, in practice this is rare. This paper discusses the methods of detecting of unknown signals, which do not require a priori knowledge of detecting signals.